Genomic Insights Into the Unique Demographic History and Genetic Structure of Five Hmong-Mien-Speaking Miao and Yao Populations in Southwest China - Yang, Meiqing; He, Guanglin; Ren, Zheng; Wang, Qiyan; Liu, Yubo; Zhang, Hongling; Zhang, Han; Chen, Jing; Ji, Jingyan; Zhao, Jing; Guo, Jianxin; Zhu, Kongyang; et al. (Frontiers in Ecology and Evolution, 2022)
Southern China was the original center of multiple ancestral populations related to modern Hmong-Mien, Tai-Kadai, Austroasiatic, and Austronesian people. More recent genetic surveys have focused on the fine-scale genetic structure and admixture history of southern Chinese populations, but the genetic formation and diversification of Hmong-Mien speakers are far from clear due to the sparse genetic sampling. Here, we reported nearly 700,000 single nucleotide polymorphisms (SNPs) data from 130 Guizhou Miao and Yao individuals. We used principal component analysis, ADMIXTURE, f-statistics, qpAdm, phylogenetic tree, fineSTRUCTURE, and ALDER to explore the fine-scale population genetic structure and admixture pattern of Hmong-Mien people. The sharing allele patterns showed that our studied populations had a strong genetic affinity with ancient and modern groups from southern and southeastern East Asia. We identified one unique ancestry component maximized in Yao people, which widely existed in other Hmong-Mien-speaking populations in southern China and Southeast Asia and ancient samples of Guangxi. Guizhou Hmong-Mien-speakers harbored the dominant proportions of ancestry related to southern indigenous East Asians and minor proportions of northern ancestry related to Yellow River farmers, suggesting the possibility of genetic admixture between Hmong-Mien people and recent southward Sino-Tibetan related populations. Furthermore, We found a genetic substructure among geographically different Miao and Yao people in Leishan and Songtao. The Yao and Miao people in Leisan harbored more southern East Asian ancestry but Miao in Songtao received more northern East Asian genetic influence. We observed high mtDNA but low Y-chromosome diversity in studied Hmong-Mien groups, supporting the role of sex-specific residence in influencing human genetic variation. Our data provide valuable clues for further exploring population dynamics in southern China.